Design of didactic guides for teachers and students from 1° to 6° levels at Exquisito Multigrade Elementary School 2011 - Araúz Castillo, Itzy Janeth; González M., Lorelaing del C.; González Ortega, Tatiana Osiris; De Gracia, Edward (David, Panamá : UDELAS, 2011)
This project was done in order to provide better support in the english teaching process for the multigrade shools. This guide is for student from 1 to 6 levels which helps in the development of the class because it will have explanations in spanish and pronunciation of the english words. This guide was organized with the program of MEDUCA and also it will count with strategies for english teaching and learning process.
Index Front Acknowledge Dedication General Index Introduction CHAPTER I CHAPTER II 2.1. Description of the proposal 2.2. Project action areas 2.3. Lines of action of project 2.4. Activities 2.4.1. Description of activities 2.4.2. Methodology tobe implement for evaluation of activities 2.4.3. Instrument or guide to be used 2.5. Schedule of activities 2.6. Organization chart 2.7. Budget 2.7.1. Human resources 2.7.2. Material resources 2.7.3. Economic resources 2.8. Evaluations 2.8.1. Evaluations guide CHAPTER III Recommendation Bibliographic Annex
Incluye Index
Documento presentado para optar por el título de Licenciatura en Docencia en Inglés
Incluye Bibliografía
No se presta a domicilio
No se saca fotocopia
Keywords: ENGLISH -- PROYECTO COMUNITARIO DE LICENCIATURA -- DIDACTICA; SPECIAL EDUCATION FACULTY; ENGLISH TEACHING DEGREE; LICENCIATURA EN DOCENCIA EN INGLÉS; EXQUISITO MULTIGRADE ELEMENTARY SCHOOL